SISTEM PEDUKUNG KEPUTUSAN KELAYAKAN DIKLAT KEPEGAWAIAN DENGAN MENGGUNAKAN ANALYTIC HIERARCHY PROCESS - Annisa Paramitha Fadillah; Rani Puspita Dhaniawaty; Risnandar Deris (LPPM STMIK STIKOM Indonesia, 2020)
Education and training is an obligation for a civil servant (PNS) to develop their performance capabilities in the agency they work for. There are several training courses that civil servants can participate in, such as leadership, functional training, and technical training. However, not all employees can participate in the training, because there are special requirements in order to participate in the training. The purpose of this study is to help provide decision recommendations for employees who will conduct training. The method used for the calculation of the DSS is Analytic Hierarchy Process (AHP). Where this decision support model will describe a multi-factor or multi-criteria complex problem into a hierarchy. Then each employee is given the weight of his own assessment of the employee who will conduct the training. Meanwhile, the system development method used is a prototype. The results of this study are in the form of a decision support system, which can facilitate the decision-making process, and can provide recommendations regarding employees who will become training participants.